(untitled) (Pedagogical Horizons, 2021)
The self-presentation of politicians is an inherent component of the contemporary media landscape. Therefore, visual literacy and art education at school are indispensable for an education towards political maturity. Especially the pictures of the New Right are challenging for school since young members of this group are very active in the field of social media, which makes them very attractive for young people. This is why the functionality as well as the effectiveness of such pictures are analyzed with reference to an exemplary Instagram account in this article. Behind this background, it is outlined how such pictures can be discussed within classes of art education. Eventually, the aim of this article is also to show the potentials of art education for political maturity and their effectiveness within interdisciplinary lessons.